Big data benchmarking : 6th international workshop, WBDB 2015, Toronto, ON, Canada, June 16-17, 2015 and 7th international workshop, WBDB 2015, New Delhi, India, December 14-15, 2015 : revised selected papers /: 6th international workshop, WBDB 2015, Toronto, ON, Canada, June 16-17, 2015 and 7th international workshop, WBDB 2015, New Delhi, India, December 14-15, 2015 : revised selected papers. ([2016]) - Unknown
No abstract available